Development of Paralympic Sport 2008-2022 through Systematic Literature Review - Fadian, Ulfa Fatahara Laras; Hidayatullah, Mohammad Furqon; Riyadi, Slamet; Umar, Fadilah (KnE Social Sciences, 2024)
This study aims to analyze (1) the development of paralympic sports participation and achievement, and (2) the self-discovery and quality of life of athletes with disabilities through a systematic literature review (SLR). The SLR stages begin with formulating research questions, conducting a literature search through the Scopus database assisted with the publish or perish application and Mendeley desktop, screening and coding selected articles, analyzing and synthesizing selected articles, conducting quality control namely selected and eligible articles, compiling discussions, and determining the validity and reliability of the data. The results of the analysis show that (1) Paralympic participation and achievements have significant results that can be observed from the enthusiasm of athletes, officials, and spectators, with millions participating in enjoying and watching the euphoria of the biggest Paralympic event, as well as increased achievements with sharpening results, time records, and even breaking records. (2) Self-discovery and quality of life: Paralympic events stimulate social development, benefit the host community, and alter public negative perceptions of disability to positive things. Disabled athletes strive for independence, quality of life, and a sense of self. A systematic review of the literature compiled in original research summarized in the Scopus database can provide an overview of developments focusing on participation, achievement, identity, and quality of life of athletes with disabilities. Overall, this systematic literature review research can become a reference for sources and further research. Keywords: athletes with disabilities, paralympic achievements, paralympic participation, paralympic sports, systematic literature review